Cross-cultural consumer behaviour towards downloading music files off the Internet. - Chin, Marianne Chui Li. (2008)
The study hopes to give marketers more insight into the downloading tendency of a consumer across different cultures and also the managerial implications for the music companies that are currently facing threats from this new trend of downloading music files off the Internet.